UTILIZAÇÃO DE SÍLICA DE CASCA DE ARROZ EM ARGAMASSAS EM SUBSTITUIÇÃO PARCIAL DO CIMENTO PORTLAND (REMUNOM, 2024)
The use of materials such as silica from burning rice husks in construction, especially to replace some of the cement in the production of cementitious composites, is a practice that contributes to environmental sustainability, since the cement industry is responsible for a substantial portion of global greenhouse gas emissions. This is due not only to the reduction in the extraction of the clinker used to make cement, but also to the use of waste from other industries. Another advantage is that the partial replacement of cement with silica can contribute to improvements in some of the properties of these composites. As a result, the purpose of this study was to analyze the mechanical and physical performance of mortars produced with 0% (reference), 5%, 10% and 15% replacement, by volume, of cement with silica from rice husk ash (SCA). Tensile tests were carried out for diametrical compression at 28 days, compression at 7 and 28 days and absorption index at 28 days of curing. The results showed that the samples with ash had similar tensile strength to the reference. In general, the introduction of SCA reduced the compressive strength values and slightly increased the absorption index of the mortars. These results are unfavorable for mechanical performance and durability, respectively, but can be mitigated by effectively grinding the ash before use. For future research, we suggest studying the performance of mortars with ash after long curing times, as the reactions of SCA occur slowly.